STRATEGI PENINGKATAN EFEKTIVITAS MANAJEMEN SARANA DAN PRASARANA LABORATORIUM IPA MENDUKUNG PEMBELAJARAN PRAKTIKUM YANG BERKUALITAS - Haristian, Amanda Dyaning; Roihanah, Nisrina Azmi; Haibah, Risti Nisrina; Margaretta, Desyana Olenka (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2025)
This study aims to examine in depth the strategy to improve the effectiveness of science laboratory facilities and infrastructure management that can support quality practicum learning. Through literature review and literature review, this study analyzes various literature on the definition, function, role of science laboratory facilities and infrastructure management, strategies to improve the effectiveness of laboratory management, as well as inhibiting and supporting factors for the management of science laboratory facilities and infrastructure, and the impact on the quality of practicum learning. The results of the study indicate that the effectiveness of laboratory management is generally influenced by many factors, one of which is the availability of laboratory facilities and infrastructure that meet standards. Management of science education laboratory facilities and infrastructure is very important to support practicum activities in schools, with good management can increase the efficiency and effectiveness of practicums.